Associations among Gender, Coping Patterns and Functioning for Individuals with Chronic Pain: A Systematic Review - Nina El-Shormilisy; Jenny Strong; Pamela J Meredith (Pain Research and Management)
BACKGROUND: Developing strategies for coping with chronic pain is an integral part of successfully living with this often debilitating health condition. While gender differences in pain coping strategies have long been investigated, the relationship between gender-specific engagement in coping and associated functioning in individuals experiencing chronic pain is yet to be clearly understood.